Faktor Risiko Kejadian Keracunan Pestisida Organofosfat pada Petani Hortikultura di Kecamatan Ngablak Kabupaten Magelang, 2008 - Asror, Farikhun; Sulistiyani, Sulistiyani; Hanani D., Yusniar (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2007)
ABSTRACT Background: Pesticides spraying which is not follow the regulation, will give many effect on human health. Many adverse effects on human health include anemia, neurodegenerative diseass, endocrine disruption caused by chronic poisoning of pesticides on farmers. Pesticides poisoning can be detected by the examination of the blood cholinesterase activities. Factors that influence to the occurrence of pesticides poisoning are the factors from the inside of the human body ( internal) and outside of the human body ( external) The objective of this research was determined risk factors of organophosphate pesticides poisoning on the horticultura sprayer farmers in agriculture area of Tejosari village, Ngablak Sub- distric , Magelang. Method: This research used case control design study, with 100 samples included of cases 50 and controles 50. The population was sprayer farmers and sprayer farmer labour of horticultura agriculture area of Tejosari. Data was analyzed by univariate analysis by using table of frequency distribution and analyze the percentage, bivariate analysis by using statistical test of Chi-square and multivariate analysis by using statistical test of logistic regretion. Result: Total respondens base on group of age mostly 35 – 44 ages (31%), respondens level of education which graduated from elementary school (76%). From multivariate analisis showed that risk factors for pesticides poisoning were less knowledge (p = 0,041; OR: 3,630; 95% C.I : 1,057–12,529); abnormal nutrition status (p = 0,048; OR: 6,623; 95% C.I. : 1.015–43.204); anemia (p = 0,009; OR : 5,987; 95% C.I. : 1,564-22,914); using of personal protective equipment not complete (p=0,001 OR : 26,661; 95% CI : 5,841-121,705) and over dose pesticide (p = 0,003; OR 8,095; 95% C.I. 2,055-31,883). Conclusion : using of personal protective equipment complete was the most influence risk factor to the occurrence of organophosphat pesticide poisoned at the horticultura sprayer farmers of plant pest. It is suggested that the sprayer farmers have to use complete personal protective equipment each time used pesticides. Key Words : Risk factor, Cholinesterase activities, Organophosphat the pesticide poisoning